An Analysis of Students’ Reading Strategies in Understanding English Text at First Semester Students of STIE-SAK Academic Year 2025/2026 - Yelnim, Yelnim; Kartawijaya, Sukarta (The Future of Education Journal, 2026)
In this research, the writer used descriptive research to analyze the students’ reading strategies in reading English text at first semester students of STIE-SAK academic year 2025/2026. This research was done in order to get description about students’ reading strategies used by the students in reading English text. The population of this research was the students at first semester of Development economics of STIE-SAK academic year 2025/2026. The instruments of this research were questionnaire. Based on the research findings in the previous chapter, the researcher could draw a conclusion that the students were dominantly used reading strategies because there were 82,35% of students had positive responses. In pre-reading stage, it was found that there were 46,1% in “always” option, 26,3% in “usually option, 19,7% in “sometime” option, 3,9% in “seldom” and “never” option. During reading, there were many responses chose by students in “always” option. It was about 42 responses in “always” option, 39 responses in “usually” option, 25 responses in “sometime”, 18 responses in seldom, and 9 responses in “never” option. Furthermore, the result of the students’ responses in post-reading was dominant in “usually” option. There were 26 responses in “always”, 46 responses in “usually”, 18 responses in “sometime”, 7 responses in “seldom”, and 17 responses in “never”. The researcher could draw a conclusion that the students used reading strategies in reading English text.